Scheduling with sequence-dependent setup times in short-term production planning: A main path analysis-based review - Kuo-Ching Ying; Pourya Pourhejazy; Zhi-Rong Lin (Operations Research Perspectives)
The role of setup times in production planning and control was recognised in the late 1960s. Since then, a growing number of scheduling problems have accounted for sequence-dependent setup time variables. This study aims to provide a systematic review of setup times in the short-term production planning literature, using an objective, algorithm-based approach. The Main Path Analysis (MPA) and Cluster Analysis (CA) methods are employed to identify patterns of knowledge development and the most significant advancements in the field. Over 2100 articles published between 1986 and 2024 were considered in the review. The seminal articles contributing to the advances in setup times for production scheduling are reviewed. Meanwhile, the core optimisation technologies, model characteristics, and emerging issues at different stages of literature development are discussed. The key extensions of the main path are further explored to identify secondary research interests in the field. Twenty-two research themes were identified to provide an overall perspective and shed light on the technical features and challenges. Finally, future research directions are suggested based on the outcomes of this systematic review.